THERMOELECTRIC DEVICES FOR CONTRAST THERMAL EFFECT ON THE INDIVIDUAL ZONES OF THE HUMAN BODY - O. V. Evdulov; A. R. Bazaev (Вестник Дагестанского государственного технического университета: Технические науки)
The article considers various design options for devices contrast to the thermal effect on the individual zones of the human body.